2021
DOI: 10.25122/jml-2020-0011
|View full text |Cite
|
Sign up to set email alerts
|

A review of peripherally inserted central catheters and various types of vascular access in very small children and pediatric patients and their potential complications

Abstract: Accessing the veins for blood delivery, sampling or nutrition is a critical factor in the process of care and management of pediatric patients. In this regard, the peripherally inserted central catheter (PICC) is one of the main alternatives which could be applied effectively as traditional central venous devices in neonates and adults. Due to their essential role in providing safe central venous entry, PICCs could be applied extensively in patients who are critically ill. The main aims of the present study ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0
35

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(73 citation statements)
references
References 73 publications
2
36
0
35
Order By: Relevance
“…The growing number of chronic kidney diseases in the elderly population led to March 13, 2014 being designated as "World Kidney Day and Chronic Kidney Disease in the Elderly" to highlight the importance of aging and the possibility of developing chronic kidney disease [40]. And if people do not pay attention to the health of their kidneys, especially in people over 50, in the coming years, we will see a dramatic increase in the number of patients with chronic kidney disease [41][42][43][44]. Studies show that hemodialysis patients are at risk for cognitive impairment and the prevalence of cognitive impairment in ESRD patients undergoing hemodialysis is reported to be between 30-60%.…”
Section: Importance and Necessitymentioning
confidence: 99%
See 1 more Smart Citation
“…The growing number of chronic kidney diseases in the elderly population led to March 13, 2014 being designated as "World Kidney Day and Chronic Kidney Disease in the Elderly" to highlight the importance of aging and the possibility of developing chronic kidney disease [40]. And if people do not pay attention to the health of their kidneys, especially in people over 50, in the coming years, we will see a dramatic increase in the number of patients with chronic kidney disease [41][42][43][44]. Studies show that hemodialysis patients are at risk for cognitive impairment and the prevalence of cognitive impairment in ESRD patients undergoing hemodialysis is reported to be between 30-60%.…”
Section: Importance and Necessitymentioning
confidence: 99%
“…The prevalence of cognitive impairment and dementia in patients with endstage renal disease is twice as high as in the elderly who do not have chronic renal failure. Cognitive impairment in these patients is not limited to stage 5 disease and may occur in the early stages of the disease [42][43][44]. Early detection of cognitive disorders and timely treatment in the early stages of the disease can largely prevent possible consequences by slowing its progression, reducing treatment costs, and reducing the pressure and burden of the disease on others.…”
Section: Importance and Necessitymentioning
confidence: 99%
“…A new study on patients with the coronavirus in China found a link between blood types A-B-O and the coronavirus [1][2][3]. According to experiments, whether people with different blood types have more complications of coronary heart disease or whether the owners of this blood type suffer from higher mortality than others is an unknown and under investigation [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Inflammatory responses play an important role in the progression and instability of atherosclerosis and cardiovascular disease [1,2]. The development of neointimal proliferation due to inflammation is the leading cause of stent restenosis [3].…”
Section: Introductionmentioning
confidence: 99%